Sweet and cool dangers of vape - Look, Keyun; Ser, Hooi Leng *; Amar, Daud Iskandar Abdullah *; Elil, Renganathan *; Long, Chiau Ming * (Star Media Group Berhad, 2023)
Lack of regulation on vaping is a critical concern, especially considering the increasing popularity of vape products with cooling flavours among young adults. These flavours may escalate the frequency of vaping and potentially lead to nicotine dependency. It is essential to dig deeper into the constituents of these products and understand their potential health effects.